Dental anxiety and its impact on oral health-related quality of life among Indonesian children aged 8–12 years: a cross-sectional study - Anisyah, Ika; Oewen, Roosje R.; Triani, Rini; Sasmita, Inne S.; Andiesta, Niekla Survia (Padjadjaran Journal of Dentistry, 2025)
Introduction: Dental anxiety in children is a common problem that affects their oral health-related quality of life (OHRQoL). It may persist into adulthood and become chronic. This study aimed to examine the relationship between dental anxiety and OHRQoL in children aged 8–12 years. Methods: A cross-sectional study was conducted on 199 children at Baitul Maal Islamic Elementary School, Jakarta. Dental anxiety was measured using the Children’s Fear Survey Schedule-Dental Subscale (CFSS-DS), and OHRQoL was assessed using the Child Oral Health Impact Profile-Short Form 19 (COHIP-SF19). Data were analyzed descriptively and with Pearson’s correlation analysis. Results: A total of 19.1% of children reported dental anxiety and 23.1% had poor OHRQoL. Pearson’s test revealed a significant but weak negative correlation between dental anxiety and OHRQoL (r = -0.148; p = 0.018), with R2 explaining 2.19% of the variance. Conclusion: Dental anxiety is associated with poorer OHRQoL; higher dental anxiety is associated with lower OHRQoL in children and accounts for approximately 2.19% of the variance in OHRQoL. Early interventions are essential to reduce anxiety and improve oral health outcomes.